Satchidananda sutras jewels from the teachings of Sri Swami Satchidananda - Satchidananda, Swami, 1914-2002.; Barsel, Lakshmi; Barsel, Paraman (Buckingham, Va. : Integral Yoga Publications, 2011)
Subtitled ?Jewels from the Teachings of Swami Satchidananda,? this booklet collects hundreds of this great Yoga Master?s seminal teachings in pithy aphorisms in his own words like ?You are happiness personified? and ?Renounce the selfishness and you will be in Bliss.? Each of these gems is capable of guiding a lifetime. Organized into 28 topics including Happiness and Fun, Faith, Love, Mind, Spiritual Practice, Meditation, Mantra, Marriage/Relationships, Prayer, Renunciation, Divine Will, Emotions, Willpower, Beauty & Art, Pranayama, Yoga of Wisdom, Guru, Body & Health, and Life and Death. Essential wisdom for all aspects of life? inner and outer.
Keywords: Yoga; PHILOSOPHY / Eastern; RELIGION / Hinduism / General; Electronic books